MULTIKULTURALISMEDALAM SASTRAKONTEMPORERAMERIKA Analisis Kumpulan Cerita Pendek Karya Brian Leung - Laksono, Arido (Sabda: Jurnal Kajian Kebudayaan, 2013)
The understanding towards values, norms ana culture of societies is a crucial matter nowadays considering the close distance among countries in the world. This phenomenon is undoubtedly considered as the result of the advancement of technology distributed and understood by people around the world as a big leap to comprehend societies with their various culture and customs. Thus, the understanding towards multiculturalism is an important issue in global societies to avoid prejudice and stereotypes of other ethnic and tribes. One of the ways is studying the values of multiculturalism either implicitly or explicitly through the work of literature as a reflection of human life. Literary work is regarded as an excellent medium for studying the richness of human nature and its culture considering the fact that only a few people are fortunate to have the opportunity to see and experience other culture. Time and capital constraints have given literary work spaces to accommodate someone's interest in experiencing values, norms and culture of other societies in different areas of the world.